Effects of Drumstick Tree (Moringa oleifera) and Lemongrass (Cymbopo-gon citratus) Leaf Extracts on the Growth Performance of Chickens - Moniño, Analyn M.; Moniño Jr., Primitivo D.; Ibañez, Jr. , Roger Y. (Future Science / FSH-PH Publications, 2023)
This study aimed to investigate the impact of drumstick tree and lemongrass leaf extracts on the growth performance and economic returns of broilers and kabir chicks by administering the two leaf extracts in their drinking water. A total of 90 straight-run day-old broilers and 90 Kabir chicks were used, and a two-factor complete randomized design factorial experiment with three treatments and six replicates was employed. The birds' weights were measured at one day old, 21 days, and 35 days to determine their body weights and weight development, while feed consumption, feed conversion efficiency, dressing percentage, and livability rates were also measured. Duncan's Multiple Range Test was used to analyze the data. The results revealed that the birds on the control treatment (T0) exhibited inferior performance in all parameters compared to those on T1 and T2. The addition of lemongrass and drumstick tree leaf extract (10ml/liter) to chicken drinking water resulted in reduced feed consumption and improved feed conversion efficiency. The treated chicken also exhibited greater dressing percentages (with or without giblets). At the end of the trial, the cumulative livability rate in the treatment group was significantly (P<0.01) higher than that in the control group. These findings suggest that lemongrass and drumstick tree leaf extracts can promote chicken development.